2020
DOI: 10.7554/elife.55305
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained repeated pregnancy loss is associated with altered perceptual and brain responses to men’s body-odor

Abstract: Mammalian olfaction and reproduction are tightly linked, a link less explored in humans. Here, we asked whether human unexplained repeated pregnancy loss (uRPL) is associated with altered olfaction, and particularly altered olfactory responses to body-odor. We found that whereas most women with uRPL could identify the body-odor of their spouse, most control women could not. Moreover, women with uRPL rated the perceptual attributes of men's body-odor differently from controls. These pronounced differences were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Typically, imprinting involves linking a stereotyped and robust response to a complex stimulus that is a priori unknown. Among the best-known and most widely replicated examples of imprinting in mammals is the Bruce effect (BE), first described and repeatedly shown in various forms in mice ( Bruce, 1959 ; Brennan and Keverne, 1997 , Brennan, 2009 ) and later demonstrated or implicated in other species ( Roberts et al, 2012 ; Eleftheriou et al, 1962 ; Clulow and Langford, 1971 ; Mallory and Brooks, 1980 ; Packer and Pusey, 1983 ; Rozenkrantz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, imprinting involves linking a stereotyped and robust response to a complex stimulus that is a priori unknown. Among the best-known and most widely replicated examples of imprinting in mammals is the Bruce effect (BE), first described and repeatedly shown in various forms in mice ( Bruce, 1959 ; Brennan and Keverne, 1997 , Brennan, 2009 ) and later demonstrated or implicated in other species ( Roberts et al, 2012 ; Eleftheriou et al, 1962 ; Clulow and Langford, 1971 ; Mallory and Brooks, 1980 ; Packer and Pusey, 1983 ; Rozenkrantz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We used a previously described shirt sniffing device (SSD) ( 53 ) to standardize body-odor sampling. The SSD consists of a glass jar containing the T-shirt, with an air intake port via soda lime filter, and air sampling port via one-way flap valve into individual-use airtight nose mask ( 53 ). Using the SSD assured that environmental odors, and/or other participant odors, did not contaminate the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Triangle test: The 40 T-shirts of the click dyads were thawed at room temperature 1 hour before the smelling experiment. We used a previously described shirt sniffing device (SSD) (53) to standardize body-odor sampling. The SSD consists of a glass jar containing the T-shirt, with an air intake port via soda lime filter, and air sampling port via one-way flap valve into individual-use airtight nose mask (53).…”
Section: Harvesting Body-odor From Click-dyadsmentioning
confidence: 99%
“…Studies have also shown that underarm odors of men stimulate the secretion of luteinizing hormone in women and increase the feeling of relaxation [476], indicating that odors affect mood. Women who experience unexplained repeated pregnancy loss had an altered olfactory sense and olfactory responses to men's body odors [477], suggesting that olfactory sense affects the process of pregnancy as well. Studies on embryos and neonates have shown that odors play significant roles from early stages in life to adolescence affecting our physiological condition, our emotions, and behaviors [478].…”
Section: Phytochemicals For Neuropharmacological Effectsmentioning
confidence: 99%